Inclusive Teaching: Adapting Content and Delivery for Diverse English Learners - Malihah, Salsabila; Safriyani, Rizka; Anifaturohmaniah (ICONELT, 2024)
This qualitative case study examines the impact of differentiated instruction on student engagement and learning outcomes across a variety of classroom environments. Qualitative study methodology was used to collect data, including observations of classroom environments and evaluations of student work. The study found that differentiated instruction can produce significant and positive changes. Assignments that are tailored to each student’s abilities and learning preferences result in higher levels of engagement and understanding. Teachers found that a variety of instructional strategies were effectively tailored to students’ preferred learning styles, fostering a more inclusive and engaging learning environment. However, this research also identifies factors, such as teacher training duration and professional development strategies, that are aimed at ensuring implementation success. Despite this challenge, blended learning has proven to be quite helpful in lowering the learning curve for English and raising academic achievement. This emphasizes how important it is to give teachers support and guidance so they may successfully implement blended learning. In the end, this initiative has the potential to improve teaching practices and create a learning environment in the Indonesian context, which highlights the need for significant investments in student learning and teacher preparation.